2022
DOI: 10.3390/ijerph192315516
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Health Belief Model, Exercise, and Nutrition Behaviors during the COVID-19 Pandemic

Abstract: Introduction: The COVID-19 pandemic has affected our nation’s health further than the infection it causes. Physical activity levels and dietary intake have suffered while individuals grapple with the changes in behavior to reduce viral transmission. With unique nuances regarding the access to physical activity and nutrition during the pandemic, the constructs of Health Belief Model (HBM) may present themselves differently in nutrition and exercise behaviors compared to precautions implemented to reduce viral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
1
1
1
Order By: Relevance
“…Thus, respondents do not perceive the consistent intake of gym supplements as a preventive measure against health-related issues, which aligns with how consuming these supplements does not aid in building good health or contribute to an individual's well-being. These findings are consistent with the study by Kiely et al [74], which investigated the health behaviors of individuals during the pandemic. It was found that perceived benefit had no statistical significance toward a change in exercise behavior; individuals' perceptions of the benefits of exercise did not strongly correlate with their actual exercise behavior changes.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, respondents do not perceive the consistent intake of gym supplements as a preventive measure against health-related issues, which aligns with how consuming these supplements does not aid in building good health or contribute to an individual's well-being. These findings are consistent with the study by Kiely et al [74], which investigated the health behaviors of individuals during the pandemic. It was found that perceived benefit had no statistical significance toward a change in exercise behavior; individuals' perceptions of the benefits of exercise did not strongly correlate with their actual exercise behavior changes.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings thus run counter to previous work, which has found that the combination of susceptibility and severity did not Food consumption and perceived well-being have a strong association with healthy behavior change (e.g. Kiely et al, 2022). While risk perceptions may influence healthy food consumption practices, it appears that excessive negative emotion can motivate individuals to engage in coping behaviors that are not in their best interests.…”
Section: Moderating Effect Of Fear Of Mortality On the Link Between R...contrasting
confidence: 99%
“…Lastly, we also found that Internet use has a more pronounced impact on the younger- and middle-aged population over 35 years of age. According to the Health Belief Model, people aged over 35 years have deeper self-awareness and are more adept at using the Internet to obtain health information and improve their health level [ 60 , 61 ]. This indicates that the Internet can reduce the health disparities among residents of different ages.…”
Section: Discussionmentioning
confidence: 99%